2021
DOI: 10.48550/arxiv.2109.09100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Almost-complex invariants of families of six-dimensional solvmanifolds

Abstract: We compute almost-complex invariants h p,0 ∂ , h p,0 Dol and almost-Hermitian invariants h p,0 δ on families of almost-Kähler and almost-Hermitian 6-dimensional solvmanifolds. Finally, as a consequence of almost-Kähler identities we provide an obstruction to the existence of a symplectic structure on a given compact almost-complex manifold. Notice that, when (X, J, g, ω) is a compact almost Hermitian manifold of real dimension greater than four, not much is known concerning the numbers h p,q ∂ .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…From system (12) we can easily deduce that either B, C, D are constant or k = l = 0. If k = l = 0, then for every (0, 0) ≠ (m, n) ∈ Z 2 system (11) can be rewritten as…”
Section: ∂ Of Two Almost Hermitian Structures On a Hyperelliptic Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…From system (12) we can easily deduce that either B, C, D are constant or k = l = 0. If k = l = 0, then for every (0, 0) ≠ (m, n) ∈ Z 2 system (11) can be rewritten as…”
Section: ∂ Of Two Almost Hermitian Structures On a Hyperelliptic Surfacementioning
confidence: 99%
“…In the remaining case when the almost Hermitian metric is not locally conformally almost Kähler, in general not much is known. For other recent and related results concerning the study of the spaces of harmonic forms on compact almost Hermitian manifolds, see [2], [8] and [12] for Dolbeault harmonic forms, and [6], [9] and [10] for Bott-Chern harmonic forms.…”
Section: Introductionmentioning
confidence: 99%
“…By a direct computation the structure equations become (cf. also [13]) First, we do the following observation that will allow us to work with only leftinvariant forms (cf. [1, Lemma 5.2]).…”
Section: Bcmentioning
confidence: 99%
“…With different techniques in [15] it was shown that also the dimension of the space of ∂-harmonic (1, 1)-forms depend on the metric on 4-dimensional manifolds (for other results in this direction see [13] and [10]). We note that explicit computations of ∂-harmonic forms is a difficult task and not much is known in higher dimension (see [16], [2], [3] for some detailed computations).…”
Section: Introductionmentioning
confidence: 99%
“…By a direct computation the structure equations become (cf. also[16])4 dφ 1 = −φ 13 − iφ 23 + φ 1 3 + φ 3 1 − iφ 2 3 + iφ 3 2 + φ 13 − iφ 23 , 4 dφ 2 = −iφ 13 + φ 23 − iφ 1 3 + iφ 3 1 − φ 2 3 − φ 3 2 − iφ 13 − φ 23 , dφ 3 = 0.Endow (X, J) with the left-invariant almost-Kähler structure given by ω = 2(e 16 + e 25 + e 34 ) = i(φ 1 1 + φ 2 2 + φ 3 3).…”
mentioning
confidence: 99%